SEASONAL VARIATION INFLUENCES GLUTATHIONE MEDIATED ANTIOXIDANTS IN Donax incarnatus COLLECTED FROM THE TWO SOUTH INDIAN COASTAL REGIONS - PARTHIBAN, R.; NARAYANAN, P. C. SATHYA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Bivalves comprise the major marine fishery resource; as they are rich in biochemical composition and high nutritional values. The present work deals with studying seasonal variations in the glutathione mediated antioxidant in the edible clam Donax incarnatus collected from coastal region of muttukadu-kovalam estuary and Pulicat lake during period of one year, from May’ 2021 to April 2022. The changes were assessed in relation to the antioxidant components and the level of heavy metal accumulation. Obtained data indicated seasonal variations in the levels of antioxidant markers (reduced glutathione (GSH) content, glutathione peroxidise and glutathione s transferase (GST) activities and the concentrations of heavy metals (Fe, Pb, Cu, Cd and Co) in the bivalves were high during post monsoon season and the lowest values during monsoon. A seasonal variation in the levels of antioxidant components was observed. Among the antioxidant components GST activity was significantly modulated and has significant correlation with the heavy metal accumulation. It therefore appears that bioaccumulation of heavy metals could play a crucial role in regulating the antioxidant components of tissues of Donax species.